Metamaterials: Nonlinear Superchiral Meta‐Surfaces: Tuning Chirality and Disentangling Non‐Reciprocity at the Nanoscale (Adv. Mater. 24/2014). (June 2014) - Valev, V. K.; Baumberg, J. J.; De Clercq, B.; Braz, N.; Zheng, X.; Osley, E. J.; Vandendriessche, S.; Hojeij, M.; Blejean, C.; Mertens, J.; Biris, C. G.; Volskiy, V.; et al.
<x xml:space="preserve">Abstract</x> In work described by V. K. Valev and co‐workers on page 4074, circularly polarized light is incident on a nanostructured chiral meta‐surface. In the surface regions where the handedness of light matches that of the nanostructured unit cells, superchiral light is formed and strong optical second harmonic generation can be observed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>